Conflicts between humans and crocodilians in urban areas across Brazil: a new approach to support management and conservation - Mascarenhas-Junior, Paulo Braga; Maffei, Fabio [UNESP]; Muniz, Fabio; Freitas-Filho, Ricardo F.; Goncalves Portelinha, Thiago Costa; Campos, Zilca; Bassetti, Luis A. B. (Univ Estadual Paraiba, Editora-eduep, 2021)
Crocodilian-human conflicts, caused especially by urban expansion and habitat destruction, have been considered one of the main threats to the conservation of these species worldwide. In Brazil, such conflicts have been documented with crocodilian species all over the country. This study identified 400 conflict events in on-line journalistic news between humans and caimans within Brazilian cities between 2016 and 2021. Caiman latirostris (57.3%) was the most common species found in large urban centers in the Northeastern and Southeastern regions. Most encounters in which the date was informed were registered in the wet season (64.5%), and the rescues were mainly carried out by the environmental military police and fire brigades. We outlined management protocols to be undertaken by environmental agencies during crocodilian rescues to minimize animal stress and risk of accidents. The increasingly common interaction between humans and caimans in urban environments is an important alert to envisage best conducts for the coexistence between people and caimans in Brazil and shows the need to invest in public policies to mitigate the negative effects of urbanization on wildlife.
Keywords: Caimans; Habitat loss; Journalistic news; Fauna rescue; Urbanization